Methods for in vitro modeling of glioma invasion: Choosing tools to meet the need. Issue 11 (5th March 2020) - Dundar, Bilge; Markwell, Steven M.; Sharma, Nitya V.; Olson, Cheryl L.; Mukherjee, Subhas; Brat, Daniel J.
Abstract: Widespread tumor cell invasion is a fundamental property of diffuse gliomas and is ultimately responsible for their poor prognosis. A greater understanding of basic mechanisms underlying glioma invasion is needed to provide insights into therapies that could potentially counteract them. While none of the currently available in vitro models can fully recapitulate the complex interactions of glioma cells within the brain tumor microenvironment, if chosen and developed appropriately, these models can provide controlled experimental settings to study molecular and cellular phenomena that are challenging or impossible to model in vivo. Therefore, selecting the most appropriate in vitro model, together with its inherent advantages and limitations, for specific hypotheses and experimental questions achieves primary significance. In this review, we describe and discuss commonly used methods for modeling and studying glioma invasion in vitro, including platforms, matrices, cell culture, and visualization techniques, so that choices for experimental approach are informed and optimal. Main Points: Selection and development of the appropriate in vitro model is critical for biologically informative studies of glioma invasion. Chief considerations for in vitro modeling include the platform, matrices, cell lines and visualization techniques.